Aperfeiçoamento de cultivos de alta densidade celular de rE.coli utilizando glicerol como fonte de carbono - Sargo, Cíntia Regina (2011)
Pneumococcal diseases are a major cause of mortality worldwide. New vaccines against Streptococcus pneumoniae are been developed. The pneumococcal surface protein A (PspA) is an important pneumococcal virulence factor and a potential vaccine candidate, therefore, a recombinant fragment of PspA gene was cloned into pET37b and the plasmid was inserted into E. coli BL21(DE3) for improved protein production in high cell density cultures (HCDC). Fed-batch is the operational mode most frequently used to obtain high cell density in recombinant E. coli cultures. Before running a high cell density culture (HCDC) of E. coli, it is usually necessary to decide whether to use glucose or glycerol as carbon source in defined or complex media, with IPTG or lactose as inducing agents. Glycerol has outstanding potential as carbon source because its assimilation does not trigger undesirable metabolite formation, even when growth takes place at high rates. However, glycerol is usually simply used as a glucose substitute in media designed for the latter as carbon source. Furthermore, most of the bioreactor induction strategies have been based on a template from molecular biology shake flask expression studies. Here, both batch and fed-batch defined culture medium formulations were modified to improve performance of the process for glycerol as growth limiting substrate. The experiments were carried out in 5 L bioreactor, using an automatically controlled exponential feeding and glycerol as carbon source. The standard defined medium formulation was modified to improve performance of the process for glycerol as growth limiting substrate and induction by both IPTG and lactose was studied. Specific growth rates up to 0.57 h-1, biomass formation yield of 0.56 g DCW/gglycerol and cellular productivities around 6.0 g (DCW)/ L h were achieved in shortened rE. coli HCDC by increasing the thiamine concentration in the medium, adding phosphate salts to the feeding medium and raising the growth phase temperature to 37°C. The performance of lactose as inducer was investigated by implementing an innovative induction strategy, which consisted of addition of a lactose pulse followed by a continuous supply of lactose mixed with glycerol in the feeding solution. The results indicated similar productivity [1.3 g (DCW)/ L h], protein maximum yield (220 mgprotein/g DCW) and concentration (26 gprotein/L) when using IPTG or lactose. These values are significantly higher than some of the best reported in the literature, confirming the efficacy of the proposed biomass formation and protein production strategy. Glycerol showed outstanding performance as carbon source, enabling high growth rates without acetate formation. Together with automatic control of the exponential feeding profile, the cultivation strategy employed resulted in higher rates of cell growth and protein production, leading to shorter cultivations with higher productivities and, consequently, lower production costs. This work is an important contribution to the field of HCDC with glycerol as carbon source and lactose as inducer.